2016
DOI: 10.1016/j.jped.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a neonatal screening program for sickle-cell disease

Abstract: Coverage by the Neonatal Screening Program of Santa Catarina is good, but did not demonstrate an improvement trend over the years. The frequency of sickle-cell disease is low and lower than in the North, Northeast, and Midwest regions. The median age in days at the time of collection is older than the age recommended by the Ministry of Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
0
8
0
2
Order By: Relevance
“…A selective pressure with the evolution of the disease would have contributed to the increase in its prevalence. Results found in the literature indicate abnormal hemoglobin frequencies ranging from 0.22% to 31% [ 4 , 5 , 9 , 13 , 20 , 23 25 ]. Some of these observations are comparable to ours [ 4 , 5 ]; on the other hand, others had different results from ours [ 9 , 13 , 20 , 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A selective pressure with the evolution of the disease would have contributed to the increase in its prevalence. Results found in the literature indicate abnormal hemoglobin frequencies ranging from 0.22% to 31% [ 4 , 5 , 9 , 13 , 20 , 23 25 ]. Some of these observations are comparable to ours [ 4 , 5 ]; on the other hand, others had different results from ours [ 9 , 13 , 20 , 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of heterozygotes was 4.7% (1:27) [23]. In a study carried out in Santa Catarina, Ellen et al reported a sickle cell trait frequency of 0.8% among 730,412 children [24].…”
Section: Discussionmentioning
confidence: 99%
“…This article aims to review the relationship between sickle cell disease and the protection it generates in malaria infection, in addition to exposing the pathophysiology, treatment and mechanism of resistance of malaria in sickle cell disease patients to achieve a broader understanding of the disease Key words: Malaria; Anemia, Sickle Cell; Hemoglobin, Sickle. (MeSH) es la enfermedad hematológica hereditaria más común con una distribución heterogénea, siendo frecuentemente encontrada en la población con ascendencia africana (12,13). El genotipo predominante es el homocigoto (HbSS) (14).…”
Section: Epidemiologíaunclassified
“…Las manifestaciones clínicas de la ECF son variadas y dependen de la gravedad y el tiempo de evolución de la misma. Los pacientes heterocigotos para la HbS (HbAS) generalmente son asintomáticos, a diferencia de los homocigotos o en combinación con otra hemoglobina anómala (12,13,16). La principal manifestación de esta enfermedad son las llamadas crisis drepanocíticas, las cuales se caracterizan por crisis vasooclusivas, dolorosas y recurrentes (30).…”
Section: Características Clínicasunclassified